Institutional reform for irrigation and drainage : proceedings of a World Bank workshop - Gonzalez, Fernando J.; Salman, Salman M. A.; World Bank. (Washington, D.C. : World Bank, 2002)
This report consists of selected papers and presentations discussed in the Institutional Reform for Irrigation and Drainage Workshop held at the World Bank in Washington DC on December 11, 2000. It consists of an introduction and three separate but inter-related parts
Selected papers and presentations discussed at a workshop held at the World Bank in Washington, D.C. on December 11, 2000.
Includes bibliographical references.
osc 28/10/2021
Loans
Keywords: Irrigation; Irrigation; Drainage; Drainage